The “Rules of Engagement”: A Socio-legal Framework for Improving Community Engagement in Natural Resource Governance - Tanya Howard (Oñati Socio-Legal Series)
Increasing community action in natural resource governance is commonly seen as a pathway for improving decision making, enabling increased on-ground activity and facilitating widespread acceptance of government and industry legitimacy in managing natural resources. Other perspectives on community engagement see the promise of enriching existing or emerging democratic values by addressing the limitations of representative governance. While the practice of community engagement has been well described, more work needs to be done to understand the institutional factors that contribute to the expectations attached to these practices, and how the role of community in natural resource governance can be improved.